Rancang Bangun Sistem Informasi Manajemen Pelaporan Proyek Konstruksi Jalan Menggunakan Website - Latifah, Ayu; Ruslam, Alam (Jurnal Algoritma, 2025)
Manual reporting of road construction projects often causes delays, data errors, and difficulties in real-time monitoring. This study aims to design and build a web-based project reporting management information system to overcome these problems. The system was developed using the Rapid Application Development (RAD) methodology with the Laravel 10 framework and MySQL database, facilitating two user roles: Admin as supervisor and Implementer as field reporter. The main features that were successfully implemented include project management by Admin, digital cash book recording, detailed daily physical progress reporting, and photo documentation uploads by Implementers. Black box testing results show that all system functionalities are valid. The resulting system provides a centralized platform that significantly improves efficiency, transparency, and accountability in construction project management, making it a practical and relevant solution for small-scale projects.